Draft Seventh Five Year Plan 1985-90 - Planning Commission (Planning Commission, 1985)
The guiding principles of the Approach to the National Seventh Five Year Plan are Food, Nork and Productivity. Consistent with this, the broad locus of Karnataka's Seventh Plan will be aimed at accelerating the growth of the State economy; alleviating poverty and other acute forms of deprivation; reinforcing the provision of social goods and services; reducing inequalities by providing economic opportunities for socially disadvantaged groups; and consolidating the efforts of past investments by emphasising productivity and efficiency. A crucial instrument tor the attainment of these objectives will be the expansion of productive employment opportunities within the economy.
Government of Karnataka Planning Department